Comparison Between 2 Types of Radiofrequency Ablation Systems in Arthroscopic Rotator Cuff Repair: A Randomized Controlled Trial. Issue 4 (1st April 2019) - Faruque, Ryan; Matthews, Brent; Bahho, Zaid; Doma, Kenji; Manoharan, Varaguna; Wilkinson, Matthew; McEwen, Peter
Background: Radiofrequency ablation is commonly used in arthroscopic rotator cuff repair (RCR). New technology devices incorporating a plasma bubble may generate lower intra-articular temperatures and be more efficient. Purpose: To compare a plasma ablation device with a standard ablation device in arthroscopic RCR to determine which system is superior in terms of intra-articular heat generation and diathermy efficiency. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: This was a single-center randomized controlled trial. The inclusion criteria were adult patients undergoing primary RCR. Patients were randomized preoperatively to the standard ablation group (n = 20) or plasma ablation group (n = 20). A thermometer was inserted into the shoulder joint during surgery, and the temperature, surgery, and diathermy times of radiofrequency ablation were measured continually. Results: No significant differences were found between the standard ablation group and plasma ablation group for maximum temperature (38.20°C and 39.38°C, respectively; P = .433), mean temperature (31.66°C and 30.64°C, respectively; P = .757), minimum temperature (21.83°C and 23.45°C, respectively; P = .584), and baseline temperature (28.49°C and 29.94°C, respectively; P = .379). Similarly, no significant differences were found for surgery time (74 and 75 minutes, respectively; P = .866) and diathermy time (10 minutes for both; P = .678). Seven patients registered transient high temperatures greater than 45°C. Conclusion: There was no difference between plasma ablation and standard ablation in terms of intra-articular temperature in the joint and diathermy efficiency. Transient high intra-articular temperatures occurred in both groups. Registration: ACTRN1261300056970 (Australian New Zealand Clinical Trials Registry).